The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1017/s0952523800000559
|View full text |Cite
|
Sign up to set email alerts
|

Microphotometric, ultrastructural, and electrophysiological analyses of light-dependent processes on visual receptors in white-eyed wild-type and norpA (noreceptor potential) mutant Drosophila

Abstract: We examined a white-eyed strain of the norpA mutant (norpA;cn bw) and white (w)norpA+ controls using microspectrophotometry (MSP), electron microscopy (EM), and electroretinography (ERG). These studies revealed that light mediates receptor demise in norpA even though norpA lacks phototransduction. Rhodopsin and the rhabdomere which houses it decrease with increasing age in norpA but not in w with rearing on a 12 h light/12-h dark cycle or in constant light. At higher temperature in norpA;cn bw and w reared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…Figure 7( A) shows, in addition, that the crosssectional area of wild-type R1-6 rhabdomeres increases considerably (by about 38% in this sample) between 0 day and 1 week posteclosion. This finding may be the structural basis of the persistent finding in this laboratory (N. Scavarda, J. O'Tousa, L. L. Randall, unpublished data) and elsewhere (Zinkl et al, 1990) that the amount of R 1-6 rhodopsin increases substantially during the first week after eclosion in wild-type flies. The observations thus suggest that R 1-6 rhabdomeres continue to develop during this period.…”
Section: Discussionsupporting
confidence: 62%
“…Figure 7( A) shows, in addition, that the crosssectional area of wild-type R1-6 rhabdomeres increases considerably (by about 38% in this sample) between 0 day and 1 week posteclosion. This finding may be the structural basis of the persistent finding in this laboratory (N. Scavarda, J. O'Tousa, L. L. Randall, unpublished data) and elsewhere (Zinkl et al, 1990) that the amount of R 1-6 rhodopsin increases substantially during the first week after eclosion in wild-type flies. The observations thus suggest that R 1-6 rhabdomeres continue to develop during this period.…”
Section: Discussionsupporting
confidence: 62%
“…135 mmole/1 calcium, on the average, in light-raised rdgC retinae), which is about two orders of magnitude above the calcium content usually found in normal cells, reflects an active process of calcium accumulation. This is consistent with other observations indicating viability of the degenerating cells: (1) In a recent study when 10-day-old norpA flies were raised at 28°C under light-dark cycle regime, Stark and colleagues (Zinkl et al, 1990) concluded that "rhabdomeres are reduced, but cells survive and show some aspects of normal membrane turnover." (2) In 7-day-old light-raised rdgB flies, calcium spikes are recorded (Rubinstein et al, l9S9a,b;Minke et al, 1990;Sahly et al, 1992) indicating the existence of functional plasma membrane.…”
Section: The Relationship Between Calcium Accumulation In Globular Bosupporting
confidence: 89%
“…Although the defective gene products have been identified, it is not clear in any of these mutants how the defective proteins lead to retinal degeneration. In the retinal degeneration C mutant (rdgC, Steele & OTousa, 1990;Steele et al, 1992), neither inactivation nor afterpotential C mutant (ninaC, Pak, 1979;Matsumoto et al, 1987;, Porter et al, 1992Porter & Montell, 1993) and the no receptor potential A (norpA) mutant (Bloomquist et al, 1988;Ostroy, 1978;Meyertholen et al, 1987;Zinkl et al, 1990) the photoreceptors show normal (or close to normal e.g. norpA, Pak, 1975) morphology in young, dark-raised mutants while a few days of intense illumination induce degeneration (Steele & Reprint requests to: Dr. Baruch Minke, Department of Physiology, The Hebrew University-Hadassah Medical School, Jerusalem 91120, Israel.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to those in humans, fly mutations in phototransduction molecules including rhodopsin (Leonard et al, 1992; Kurada and O'Tousa, 1995; Iakhine et al, 2004), PLC (Meyertholen et al, 1987; Zinkl et al, 1990; Alloway et al, 2000), TRP (Hong et al, 2002; Wang et al, 2005) and arrestins (Dolph et al, 1993; Satoh and Ready, 2005) all cause age-dependent photoreceptor degenerations, which are generally characterized by diminished rhabdomeres. Several other visual proteins such as a diacylgrycerol kinase RDGA and a rhodopsin phosphatase RDGC are also essential for photoreceptor protection (Masai et al, 1993; Kiselev et al, 2000).…”
Section: Introductionmentioning
confidence: 94%